Short Report. An innovative training programme for families of children and adolescents with Autism Spectrum Disorder in Qatar: Parents as interventionists - Manal Osman Abouelseoud (17346868) (2022)
Introduction Previous research has established the association of maladaptive behaviours exhibited by individuals with Autism Spectrum Disorder (ASD) with an increase in the extent of care burden among their caregivers. The mental health needs of caregivers and their effective management, therefore, need to be given due consideration. The main aim of this paper is to reiterate the significance of the role of training programmes for caregivers in enhancing their knowledge and enabling them to manage behavioural challenges with more independence and confidence. Methods The aims, structure, and content of the ASD training programme for caregivers implemented by the specialist child and adolescent mental health service, Hamad Medical Corporation, are described. Sixty families have benefited from this initiative so far. A summary of the feedback provided by forty caregivers, all biological parents, is also summarised. Results The mean score related to knowledge among participants before and after attending the training increased from 3.28 to 4.41. Out of the 40 parents who provided feedback, 27 (67.5%) reported an increase in their understanding of the topic after attendance. Conclusion This initiative consolidates the significance of programmes focusing on enhancing awareness and improving coping among caregivers of children and young people with ASD. Other Information Published in: Research in Developmental Disabilities License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ridd.2022.104368